Experimental and numerical investigation into the effect of surface roughness on particle rebound - Altmeppen, Johannes; Sommerfeld, Heike; Koch, Christian; Staudacher, Stephan (Frontiers in Mechanical Engineering, 2022)
The abstract has been paraphrased and revised in accordance with the editor's requirements and requests for changes. It can be found in the attached tex or pdf file. Unfortunately, it is a few words too long after implementing the requested changes. We kindly ask you to accept this version.